Pragmatic modernism - Schoenbach, Lisi (Modernist literature & culture., 2012)
'Pragmatic Modernism' traces an alternative strain of modernism influenced by pragmatist philosophy and characterized by its commitment to gradualism, continuity, and habit rather than spectacular events and radical rupture.